2014
DOI: 10.1007/s13197-014-1365-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of drying kinetics of untreated and pretreated cocoyam slices

Abstract: The effect of pretreatment and drying temperature on the drying kinetics and quality of cocoyam was investigated in this study. The best model to predict the drying kinetics was also determined. Cocoyam slices were pretreated by water blanching (WB) and soaking in sodium metabisulphite (SM) and dried in a hot air oven at temperatures of 50, 60 and 70 °C while untreated samples were sun dried. Seventhin layer drying models (Exponential, Generalized Exponential, Page, Logarithmic, Parabolic, Wang and Singh and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
8
29
0
Order By: Relevance
“…The doses of OEO were 1.5, 3, and 6 mL. The MR decreased exponentially with time in all the treatments used which is consistent with the results reported in former studies (Afolabi et al 2015;Cheng et al 2015;Ismail et al 2015;Kucerova, Hubackova, Rohlik, & Banout, 2015). In Figure 1a, it might be seen that between the OT treated samples the dose of OEO affects the drying time, and even for 6 mL OEO the drying rate was slightly higher as compared to other doses in the initial period of drying, but no significant differences (p > .05) were found compared to samples treated with the other doses and the untreated control, which means that the OT itself slowed down the drying process and was not affected by the OEO dose.…”
Section: Effect Of Modified Blanching By Oeo On Drying Kineticssupporting
confidence: 90%
See 2 more Smart Citations
“…The doses of OEO were 1.5, 3, and 6 mL. The MR decreased exponentially with time in all the treatments used which is consistent with the results reported in former studies (Afolabi et al 2015;Cheng et al 2015;Ismail et al 2015;Kucerova, Hubackova, Rohlik, & Banout, 2015). In Figure 1a, it might be seen that between the OT treated samples the dose of OEO affects the drying time, and even for 6 mL OEO the drying rate was slightly higher as compared to other doses in the initial period of drying, but no significant differences (p > .05) were found compared to samples treated with the other doses and the untreated control, which means that the OT itself slowed down the drying process and was not affected by the OEO dose.…”
Section: Effect Of Modified Blanching By Oeo On Drying Kineticssupporting
confidence: 90%
“…Currently, there is a new study about the use of essential oils in terms of food safety during the meat drying process (Hernández et al, ); however, there is no evidence of research about the use of modified blanching treatments, in combination with essentials oils before the drying procedure and the effect on the drying behavior of the product. There are some studies analysing the effect of blanching and dipping methods, particularly, in the drying kinetics of vegetables (Afolabi, Tunde‐Akintunde, & Adeyanju, ; Cheng, Fang, & Ruan, ; Ismail, Figen, & Pişkin, 2015; Tunde‐Akintunde, Afolabi, & Akintunde, ) but to date, there have been no published studies comparing the effects of modified blanching treatments combined with the application of essential oils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the k value corresponded to those of radiant energy ( Table 1 ). The saving in the total drying time of food with increasing energy intensity might be due to an elevation in vapor pressure inside of product with raised temperature, resulting in more rapid moisture migration to the product surface ( Afolabi et al, 2015 ). The coefficient of determination (r 2 ) of FD and Continuous IRAFD-5.0 kW/m 2 showed a good fit of 0.9555 and 0.9635 in the exponential model, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The following statistical measures were used in determining the goodness of fit for the model [2,12,39]: For the experiment, the experimental moisture content data were used to determine the moisture ratio. Thus, it was observed that Moisture Ratio (MR) depends directly on the mass (as shown in Figure 1) and inversely on time (as shown in Figure 2).…”
Section: Discussionmentioning
confidence: 99%